Group sequential comparison of positive predictive value curves for correlated biomarker data - Ye, Xuan; Tang, Larry L.; Zhu, Xiaochen (Statistics in medicine, 2020)
Clinical studies of predictive diagnostic tests consider the evaluation of a single test and comparison of two tests regarding their predictive accuracy of disease status. The positive predictive value (PPV) curve is used for assessing the probability of predicting the disease given a positive test result. The sequential property of one PPV curve had been studied. However, in later stages of diagnostic test development, it is more interesting to compare predictive accuracy of two tests. In this article, we propose a group sequential test for the comparison of PPV curves for paired designs when both diagnostic tests are applied to the same subject. We first derive asymptotic properties of the sequential differences of two correlated empirical PPV curves under the common case‐control sampling. We then apply these results to develop a group sequential test procedure. The asymptotic results are also critical for deriving both the optimal sample size ratio and minimal required sample sizes for the proposed procedure. Our simulation studies show that the proposed sequential testing maintains the nominal type I error rate in finite samples. The proposed design is illustrated in a hypothetical lung cancer predictive trial and in a cancer diagnostic trial.